2008
DOI: 10.5194/acp-8-2485-2008
|View full text |Cite
|
Sign up to set email alerts
|

Local anthropogenic impact on particulate elemental carbon concentrations at Summit, Greenland

Abstract: Abstract. Summit, Greenland is a remote Arctic research station allowing for field measurements at the highest point of the Greenland Ice Sheet. Due to the current reliance on diesel generators for electricity at Summit, unavoidable local emissions are a potential contamination threat to the measurement of combustion-related species in the air and snow. The effect of fossil-fuel combustion on particulate elemental carbon (EC) is assessed by a combination of ambient measurements (∼1 km from the main camp), a se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 4 publications
3
12
0
Order By: Relevance
“…Furthermore, the nearest station (Molodezhnaya, 67.41°S 45.51°E) is located approximately 400 km distant from Syowa Station. According to Hagler et al [2008], the atmospheric BC concentration decreased rapidly to <1 ng m −3 in the first 30 km from BC sources in the polar region. Consequently, the anthropogenic impact from the other stations was too small to make a meaningful contribution to the haze event at Syowa.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the nearest station (Molodezhnaya, 67.41°S 45.51°E) is located approximately 400 km distant from Syowa Station. According to Hagler et al [2008], the atmospheric BC concentration decreased rapidly to <1 ng m −3 in the first 30 km from BC sources in the polar region. Consequently, the anthropogenic impact from the other stations was too small to make a meaningful contribution to the haze event at Syowa.…”
Section: Resultsmentioning
confidence: 99%
“…The generator, however, is always operating. Prior work has shown that elemental carbon (EC) from camp activities causes concentrations 1.8–2.4 times higher at 1 km than 10 or 20 km from camp [ Hagler et al ., ]. While this study focused on EC as a tracer of local emissions, it raises the expectation of similar results for other atmospheric species.…”
Section: Discussionmentioning
confidence: 99%
“…Winds at Summit are not consistently steady in speed or direction, but the least frequent direction is from due north, so all atmospheric sampling has been on the southern, "upwind" side of camp. Hagler et al (2008) pointed out that, on average, during the summers of 2003 through 2006, winds arriving at the satellite camp location passed through a northern, potentially polluted, sector (defined by point sources of pollution in the camp as well as areas where heavy equipment often was operating), 19% of the time. These authors recommended use of sector control to interrupt sampling, particularly for experiments that integrated over long periods (days or longer).…”
Section: Sampling Locationmentioning
confidence: 99%
“…It should be noted that the "bad air" sector is defined conservatively, to account for mobile sources that are not always present (e.g., equipment grooming the runway or moving snow). Hagler et al (2008) observed that during summer 2006 the winds were out of the defined camp sector 21% of the time, but local pollution (identified by very large enhancements in aerosol absorption monitored continuously) impacted the satellite camp just 7.6% of the time…”
Section: Sampling Locationmentioning
confidence: 99%